Training of Digital Data Management for Academic Services - Susilo, Dahlan; Charolina, Astri; Ruswanti, Diyah (Universitas Sahid Surakarta, 2023)
In order to get the characteristics of excellent service, the academic services at Sahid University Surakarta carried out by academic staff need to be improved through a training. This training was held with the aim of improving the competence and ability of academic staff in utilizing digital technology and improving office application skills to improve the quality of academic services. The method of service applied is the method of mentoring. Participants are trained directly and assisted in carrying out their work. The results of this community service activity are an increase in participants' understanding and skills in utilizing digital technology to support academic services, the ability of participants to successfully install and configure computer devices needed to support academic services, and awareness of the importance of improving skills in managing digital technology can increase the efficiency and effectiveness of academic services.